Pneumonectomy for severe post-tuberculosis bronchiectasis: A successful of case report and review of the long-term outcome - Zulfa, Putri O.; Habibie, Yopie A. (Narra Sains Indonesia, 2023)
Limited clinical intervention studies highlight the absence of evidence-based international guidelines for effectively managing post-tuberculosis lung disease, emphasizing bronchiectasis. The aim of this study was to describe a case of left pneumonectomy for severe post-tuberculosis cystic bronchiectasis and to provide a review of the post-surgical mortality rate, complications, survival rate, and the patient's quality of life following the pneumonectomy procedure. A 36-year-old Indonesian male smoker presented with worsening breathing difficulties and fever. The patient had a history of pulmonary tuberculosis six years ago and reported negative tuberculosis tests after completing TB treatment. However, lung function of the patient progressively declined over the years. Bronchoscopy, chest X-ray, and high-resolution computerized tomography (CT) scan revealed infected cystic bronchiectasis and identified a prominent left lung collapse with calcification in the left pleura. The patient underwent left pneumonectomy through left posterolateral thoracotomy under general anesthesia. The patient was discharged after seven post-operative days with no eventful course. No further complications were found after a one-year post-surgery follow-up, and the patient returned to normal activities, improved fitness, and was fitter in daily life. Based on the literature review, post-surgical mortality rates of pneumonectomy are acceptable, with bronchopleural fistula, cardiac arrest, and thoracic hemorrhage being common causes. Yet, the chances of a complete cure are high. Complications can occur in approximately one-third of patients, including arrhythmia, pulmonary infection, fever, and wound infections. The overall 5-year survival rate following pneumonectomy is generally favorable. Regarding the quality of life, pneumonectomy can have mixed effects. While it could improve symptoms and quality of life, it may impair the quality of life for certain patients, particularly elderly patients and those with lower preoperative quality of life. Although the post-surgical mortality rate, complications, and long-term survival rates of pneumonectomy are generally satisfactory, the expectation of improved post-surgical quality of life should be discussed with the patient prior to surgery.